Pengaruh Kualitas Seresah Pangkasan Gliricidia maculata (Gamal) dan Salacca Edulis (Salak) terhadap Penghambatan Nitrifikasi dan Efisiensi Pemanfaatan N di Alfisols - Purwanto Purwanto; Didik Rohmadi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Title : The Effect of Litter Quality of Gliricidia maculata and Salacca edulis to Inhibition of Nitrification and Efficiency N Benefit in Alfisols. This research was carried out from august 2008 to February 2009. The purpose of this research were to know the effect of litter quality of Gliricidia maculata and Salacca edulis to inhibition of nitrification and efficiency N benefit in Alfisols.This research was field research with Randomized Completely Block Design (RCBD) one factor with 11 treatments that repeat 3 times become 33 trial units. This treatment use control, without litter quality + N manure, Gliricidia maculata with dose 5, 10, and 15 ton/ha + N manure, Salacca edulis with dose 5, 10, and 15 ton/ha + N manure, and combination with dose 5, 10, and 15 ton/ha + N manure. To know the effect of treatment with variable used F test 1 % and 5 %. To know the difference between treatments used DMRT 5 %. Database analysis was used Minitab, Excel, and SPSS software. The result of this research showed that the litter quality of Salacca edulis (low quality) and Gliricidia maculata (high quality) not significant inhibit and decrease nitrification. This result can be known from the effect test of potential nitrification, concentration of NH4+ and NO3- that not significant. The average of efficiency N benefit each litter quality are 0.59 % at litter quality of Gliricidia maculata (high quality), 0,669 % at litter quality Salacca edulis (low quality), and 0,667 % at litter quality of combination between Gliricidia maculata and  Salacca edulis.